Physics of coal and mining processes - Alexeev, Anatoly D. (CRC Press, 2012)
Around the world, on average, four coal miners die for each million tons of coal recovered. Improving the safety of mining work while responding to the need for increased coal production, however, is impossible without further development of the physics of mining processes. A relatively new branch of science, it tackles problems that arise during mineral products recovery, particularly safety issues such as rock failures, coal and gas outbursts, and methane explosions. The first book to present a unifying methodology for addressing problems such as outbursts and explosions of methane in coal m.